(untitled) (International Journal of Health, Animal Science and Food Safety, 2018)
The study was carried out to investigate the effect of feeding broiler chicken on different vegetable oils with feed additives on the quality characteristics of chicken meat. A total of 216 one-day-old chicks of (Hubbard) strain were randomly assigned to six dietary treatments as (2×3) factorial designs where two sources of dietary oil with three levels of commercial multi-enzyme feed additives. Treatments were: soybean oil only (T1), soybean oil+ ZAD (T2), soybean oil+ AmPhi-BACT (T3), palm oil only (T4), palm oil + ZAD (T5) and palm oil + AmPhi- BACT (T6). Results showed that feeding broiler chicken on different types of dietary oils had significant effect on the fatty acid profile of broiler chicken meat. UFA/SFA ration of broiler chicken groups (T4, T5adT6) were significantly lower compared with (T1, T2 and T3) groups. Broiler fed on soybean oil had significantly higher n-6: n-3 ration compared with broiler fed on palm oil. Regardless of the source of dietary oil, significant differences were observed in the most of fatty acid profile in the chicken meat among levels of commercial multi- enzyme feed additives. Meat of T5and T6 had the higher pH value, followed by meat of T1and T3 groups, while the lowest pH value found in meat of T2 and T4. The higher cooking loss was found in meat of T4 while, meat of T5had the lowest value. Data of chilling loss indicated that the differences between dietary treatments were not significantly different except for meat of T6 which had the higher chilling loss. No significant differences were found in color measurements between dietary treatments.